Prevalence and Risk Factors for Colonization With Extended-Spectrum Cephalosporin-Resistant Escherichia coli in Children Attending Daycare Centers: A Cohort Study in the Netherlands. (27th July 2015) - Koningstein, Maike; Leenen, Margriet A.; Mughini-Gras, Lapo; Scholts, Rianne M. C.; van Huisstede-Vlaanderen, Kirstin W.; Enserink, Remko; Zuidema, Rody; Kooistra-Smid, Mirjam A. M. D.; Veldman, Kees; Mevius, Dik; van Pelt, Wilfrid
Abstract : Background: The purpose of this study was to determine the prevalence and risk factors for colonization with extended-spectrum cephalosporin-resistant (ESC-R) Escherichia coli in daycare center (DCC)-attending children. Methods: This is a prospective cohort study including 44 DCCs in the Netherlands, combining DCC characteristics and monthly collected stool samples from their attendees, and was performed in 2010–2012. During a 22-month study period, 852 stool samples were collected and screened for ESC-R E coli . Risk factors were studied using logistic regression analysis. Results: In DCC-attending children (<4 years old), the overall prevalence of ESC-R E coli was 4.5%, and it was 8% in <1-year-old attendees. Among the 38 children carrying ESC-R E coli, the most common types were bla CMY-2 (26%), bla CTX-M-1 (16%), and chromosomal AmpC type 3 promoter mutants (13%). Extended-spectrum cephalosporin-resistant E coli was less common in DCCs where stricter hygiene protocols were enforced, eg, not allowing ill children to enter the DCC (odds ratio [OR], 0.34; 95% confidence interval [CI], 0.14–0.84), performing extra checks on handwashing of ill children (OR, 0.42; 95% CI, 0.20–0.87), and reporting suspected outbreaks to local health authorities (OR, 0.27; 95% CI, 0.11–0.69). Conclusions: The distribution of ESC-R E coli types in DCCs differs from that of the general population. Extended-spectrum cephalosporin-resistant E coli carriage in DCC-attending children is associated with the hygiene policies enforced in the DCC. Although our results are not conclusive enough to change current DCC practice beyond ensuring compliance with standing policies, they generated hypotheses and defined the degree of ESC resistance among DCC attendees, which may influence empiric antibiotic therapy choices, and tracked the increasing trend in ESC resistance.